Public Transport Arrangement: A Study of Policy Implementation in Bandung City - Harahap, Agus Supriadi (Jurnal Administrasi Publik (Public Administration Journal), 2025)
This study aims to analyze the implementation of Public Transportation Regulations in Bandung City, Indonesia. The issues focused on are the policy content and the context of its implementation. This study applies Grindle's policy implementation framework to critically examine policy implementation, exploring how political interests, administrative capacity, and institutional dynamics shape policy outcomes, dimensions often overlooked in transport policy research. This study fills a gap in urban transportation research that largely focuses on technical and infrastructure solutions. This study uses a descriptive qualitative approach using in-depth interviews, direct observation, and document analysis involving government officials, transportation operators, drivers, and users in Bandung City. The results indicate that policy implementation has not been successful for several reasons: the policy content does not accommodate the interests of the community and operators; the community is not interested in the long-term benefits of using public transportation; the anticipated changes in the policy are too broad; coordination problems between implementing agencies; and insufficient resource allocation. Policy implementation is also hampered by various contexts, namely: the existence of strong patron-client relationships between actors in channeling their economic interests; mechanisms for community engagement that have not been institutionalized; and low bureaucratic responsiveness.